ANALISIS FAKTOR–FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN HUTANG SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2013-2015) - Fita Putri Widayanti, 13.05.52.0215; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2017)
High value of the company is one of the goals of the company. The value of the company is an investor perceptions about the level of success of the company is reflected by the stock price. This study aims to investigate and analyze the influence of managerial ownership, institutional ownership and dividend policy on firm value through debt policy as an intervening variable in the manufacturing companies listed in Indonesia Stock Exchange. The population of this research is manufacturing companies listed in the Indonesia Stock Exchange (IDX) during the years 2013-2015 that reported complete annual report and published in Indonesian Capital Market Directory. Samples are included in the criteria of this study were 110 companies using purposive sampling method. This research data analysis methods using the multiple linear regression analysis by SPSS 20. The results showed that the variables of managerial ownership, institutional ownership and dividend policy does not affect the value of the company. Debt policy is not able as an intervening variable for managerial ownership, institutional ownership and dividend policy on firm value.Keywords: Firm Value, Managerial Ownership, Institusional Ownership, Dividend Policy, Debt Policy